Green Waves and Wish Lines: Derek Walcott’s Art Nouveau - Roberta Cimarosti (ZoneModa Journal, 2025)
This article is about two poems and a play by Caribbean writer and painter Derek Walcott which, published at different stages of his career, engage with Hokusai’s print Under the Great Wave off Kanagawa and Van Gogh’s canvas The Starry Night, thereby indirectly opening the core issue of fashion ever: its relationship with art. This is because these two masterpieces have been part of fashion discourse since its start in the mid-19th century when they too were created, to the present time, when swirling stars and cresting waves have become global icons worn and exhibited, cap-à-pie, in both haute couture and the mass clothing industry.